STRATEGI GURU PAI DALAM MENGATASI KEJENUHAN BELAJAR DI SMAS DIPONEGORO TUMPANG KAB. MALANG - Addin Kholisin; M.Yusuf agung Subekti (STAI Ma'had Aly Al-Hikam Malang, 2023)
The most important component in learning is the Teacher. Teachers are not only to learn, but also educate, nurture, guide, and shape students' personalities to prepare and develop human resources. The teacher's mistake in understanding the profession, resulted in a very burdensome and boring learning atmosphere. Learning saturation can attack any kind of lesson that exists in school. One of them is the Subject of Islamic Religious Education. The problem of learning saturation related to Islamic Religious Education lessons occurred at Diponegoro Senior High School in Tumpang. The type of research used is Qualitative research, with a descriptive approach. Its data collection techniques are through observation, interviews, and documentation. Its data analysis uses data reduction, data presentation, and drawing conclusions.